2008
DOI: 10.1074/jbc.m708998200
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected Functional Link between Lysosomal Thiol Reductase and Mitochondrial Manganese Superoxide Dismutase

Abstract: Gamma interferon-inducible thiol reductase (GILT) is an enzyme involved in the initial steps of antigen processing and presentation. Recently we have shown that GILT is also expressed in mouse T cells, where it exerts an inhibitory role on T cell activation. In this study, we identified mitochondrial manganese superoxide dismutase (SOD2) as one of the key intermediaries affected by GILT expression in fibroblasts. Expression and activity of SOD2 is reduced in the absence of GILT because of reduced SOD2 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…Our previous study has shown that compared with wild type (WT), GILT Ϫ/Ϫ fibroblasts display lower steady-state levels of mitochondrial SOD2 but not cytoplasmic SOD1 (17). Consequently, the levels of reactive oxygen species were higher in GILT Ϫ/Ϫ fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study has shown that compared with wild type (WT), GILT Ϫ/Ϫ fibroblasts display lower steady-state levels of mitochondrial SOD2 but not cytoplasmic SOD1 (17). Consequently, the levels of reactive oxygen species were higher in GILT Ϫ/Ϫ fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, GILT and SOD2 may interact directly in a common but minor subcellular compartment other than lysosomes and mitochondria. Even though the pathway that connects GILT and SOD2 remains to be elucidated, transfection experiments in fibroblasts demonstrate that SOD2 is a key intermediate between GILT and cellular proliferation, as transfection of SOD2 bypasses the effect of the absence or presence of GILT (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GILT is constitutively expressed in most APCs, including monocytes=macrophages, B cells (primary and cell lines), and bone-marrow derived DCs (3,25,29,30,34,36). GILT is also constitutively expressed in thymocytes (37), mature T cells (5,37), and some fibroblasts (9,64). IFN-g plays an important role in inducing expression of MHC class II and other components of the class II-restricted processing pathway, including Ii and HLA-DM (10).…”
Section: Gilt Expressionmentioning
confidence: 99%